Uso de métodos anticonceptivos asociado a la educación en salud sexual y reproductiva en adolescentes. Centro de Salud Los Trigales. Período Octubre 2023 - Febrero 2024 - Sanchez Saltos, Wilson Jackson (2024)
This study addresses the use of contraceptive methods associated with sexual and reproductive health education among adolescents. This approach responds to the growing global concern to improve sexual and reproductive health, especially among the youth population, highlighting the importance of adopting comprehensive and accessible educational strategies. Therefore, its goal was to determine the use of contraceptive methods associated with sexual and reproductive health education in adolescents attended at the Trigales Health Center during the period from October 2023 to February 2024. The research was based on a quantitative approach, favoring a cross- sectional and non-experimental field design. It focused on a population of 25 adolescents, defined by clear inclusion and exclusion criteria, without the need to apply sampling due to the manageable size of the participating population. The survey technique, through a validated questionnaire, facilitated the structured collection of data relevant for quantitative analysis. The results obtained reflect a varied demography, with a majority of adolescents between 11 and 14 years old, predominantly mixed race and urban residents, underscoring the need for educational programs adapted to this diversity. In addition, a high reception of formal education in sexual and reproductive health was evidenced, although with notable areas for improvement regarding the depth and practical application of the knowledge acquired. The latter points to the essential need to reinforce sexual education, focusing on the correct use of contraceptive methods and informed decision-making. In response to these findings, a sexual and reproductive health education program specifically adapted to the needs of the attended. KEYWORDS: ADOLESCENTS, CONTRACEPTIVES, SEXUAL EDUCATION, REPRODUCTIVE HEALTH